(untitled) (lectio difficilior, 2006)
The idea of the origin of the Song of Songs in alleged ancient fertility practices, usually called “sacred marriage” (hieros gamos), once enjoyed a wide acceptance among biblical scholars, assyriologists and historians of religion. Toward the end of the 20th century, however, the association of the Song of Songs with ancient fertility rites became a virtually antiquated point of view. At the same time, however, the relevance of ancient Near Eastern sources to the study of the Song of Songs is better acknowledged than ever. The mythological allusions in the Song of Songs have been appreciated unencumbered by the “cultic” reading, and new ways of interpreting the Mesopotamian sacred marriage have been developed. Even readings of the Song of Songs as dealing somehow with the divine-human relationship are gaining new understanding by an increasing number of scholars, some of whom would again see the newly understood sacred marriage tradition in the background of the allegorical, typological, or otherwise religious reading of the Song of Songs. All this calls for reopening the question of the relation of the Song of Songs and the sacred marriage. In this article, this is attempted by way of surveying a century of history of research, looking for new perspectives that would help to reappraise the old problem. [1]